Design of Hazardous Waste Storage Area for Fecal Sludge Briquettes by Waste Impoundment in Indonesia - Nova Ulhasanah; Dhea Umi Falentina Widanarko; Falia Ayu Erlingga; Elsyah Bhima Fitrah; Wira Aulia; Dessy Maya Sari; Ari Rahman (Journal of Sustainable Infrastructure, 2022)
The high production and sufficient calorific value content of the fecal sludge make it can be made as a raw material for producing briquettes. This supports the world's program in an effort to create alternative energy to replace fossil fuels. The purpose of this research is to design a production building and storage of fecal sludge into briquettes in a sewage treatment company so as to minimize the potential hazards of the sludge (accidents in the work placement and the negative impact on the environmenty) as flammable hazardous waste. At the beginning of the design, 3 alternative designs were assessed using the Analytical Hierarchy Process (AHP) method. the chosen alternative is alternative 3 with the proposed redesign of the briquette storage building, production site, and fecal sludge storage area separately, where the sludge storage area which was originally a hangar was converted into a waste impoundment system. The building design criteria for alternative 3 are fire-resistant buildings whose specifications are regulated by the Indonesian National Standard 03-1736-2000 and several other regulations (PERMENLHK No. 12, 2020 and BAPEDAL No. 1, 1995). With a planned storage duration of 1 year, the waste impoundment is designed to cover an area of 2304 m3 of fecal sludge, 72 storage drums for carbonated sludge, and 95 storage drums for fecal sludge briquesttes. In addition, the waste impoundment design is based on the PERMENLHK standard No. 12 of 2020. Waste impoundment can reduce the pH and Total Suspended Solid (TSS) of hazardous waste to below the quality standard threshold. the acidity level of the waste can be neutral to pH 7.79 (threshold 6-9), and TSS down to 86.67 mg/l (threshold 200 mg/l). The results of this study can make a major contribution to the field of hazardous waste management, especially fecal sludge, not only for Indonesia but also for countries that have similar conditions.